Platelet distribution width (PDW) and platecrit (PCT) as the new biomarkers of the myocardial infarction - Katarzyna Inglot; Katarzyna Maria Sawicka; Agnieszka Zwolak; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Introduction Despite the advancement of medicine in the field of diagnostics and treatment of myocardial infarction, the annual mortality rate exceeds 40%, which is why it is still being strived to develop better and more specific markers of myocardial damage, which would allow for faster diagnosis and thus would improve the prognosis in this group of patients. Objective The objective of the study was to assess the relationship between the platelet with distribution (PDW) and plateletcrit (PCT) and the occurrence of myocardial infarction. Results People who suffered from a heart attack had higher PLT and PCT values than those who did not. Conclusions Author study research has not confirmed the relationship between PDW and PCT and the occurrence of myocardial infarction. Keywords: myocardial infarction